INFLUENCE OF ANTIOXIDANTS AND ENTEROSORBENT ON MORPHOLOGICAL STATE OF DUODENUM WALL IN EXPERIMENTAL PANCREATITIS - Шутурма, О.Я. (World of Medicine and Biology, 2014)
In the experiment on white rats there were established histological features and morphometric changes in the wall of the duodenum in experimental pancreatitis and in terms of correction. As a corrective factores we used a combination of combined carbon sorbent HSHD and antioxide - vitamin complex Livolin forte. The obtained results show the relative normalization of morphometric parameters already on 7th day of the experiment.